Hubungan Keterikatan Tempat Terhadap Minat Kedatangan Pengunjung Di Bangunan Alih Fungsi Komersial - Mona Anggiani; Dea Putri Ghassani (RUAS, 2022)
Old buildings in big cities, began to be looked at by architects for reuse. In addition to having historical value, using old buildings also saves material exploration. The use of recycled buildings has its own charm for visitors, because it can bring to the atmosphere of the past. The high interest of the public to visit the old building does not guarantee repeated re-visits, due to the factor of a sense of attachment to the place (place attachment). Attachment to one place needs to be considered to maintain the continuity of activities. This study aims to determine the relationship of place attachment to the interest in visitor arrivals in old buildings that have been converted. The object of the study was conducted in recycled buildings in the city of Jakarta, namely M Bloc Space, Kapitan Lim, and Pantjoran Tea House. This research uses non-experimental quantitative correlation research methods. Data is collected through questionnaires to visitors, then analyzed with a descriptive approach.   The results of the study stated that there is a very close relationship between the attachment of the place to the interest in visiting the building. The results of this study can be considered for planning and designing a function transfer building.